Comparison of strengthening methods to improve punching behavior of two-way RC flat slabs - Mercimek, Omer; Ghoroubi, Rahim; Erbaş, Yaşar; Anil, Ozgur; Erbaş, Yaşar (Elsevier Science Inc, 2022)
Within the scope of this study, three different strengthening methods have been proposed to increase the punching strength of reinforced concrete (RC) flat slabs. These methods are a shear stud, fiber-reinforced polymer (FRP), and textile-reinforced mortar (TRM). Ten large-scale RC flat slabs were produced to investi-gate the effectiveness of strengthening methods. One of these was chosen as a reference, one strengthened with shear stud, four strengthened with FRP and the rest with TRM. Reinforcement type (shear stud, FRP, and TRM), strip direction (straight and diagonal), and anchor usage were determined as experimental variables. The ulti-mate load capacity, initial stiffness, and energy dissipation capacity values were calculated and compared using the load-displacement graphs obtained as a result of the tests of specimens. According to the experimental results obtained, TRM, FRP, and shear stud methods increased the ultimate load capacity by an average of 58%, 52%, and 20%, respectively. These increased values for energy dissipation capacity are 118%, 63%, and 47%, respectively. In the numerical part of the study, the experimental study was simulated with the ABAQUS/Explicit FEM program, and the obtained results were compared with the experimental results. Moreover, the stresses and damage distributions in the specimens were evaluated. As a result of the study, it was seen that the method applied using textile reinforced strips gave the most successful results among three different strengthening techniques applied to improve the behavior of RC slabs under the effect of punching loading.
Keywords: Two Way Rc Slab; Strengthening; Punching; Abaqus